SCIENTIFIC AND PEDAGOGICAL WORKERS AND ADMINISTRATIVE STAFF: CONFLICT OF INTEREST OR CONSTRUCTIVE INTERACTION? - Ashot R. Alaverdov; Natalia V. Gromova (Высшее образование в России)
The article discusses the effectiveness of the system of university internal management providing the interaction of two structural units of an educational institution - chairs and managerial staff. This system is characterized by the internal contradictions decreasing its effectiveness. These contradictions are due to the conflict of interest between two main groups of workers. The author analyzes the causes, forms and the negative consequences of this conflict. The paper gives recommendations aimed at the prevention of such negative phenomena in the practice of University management through the use of complex methods of administrative, economic and psychological character.